Acquired perforating dermatoses show increased levels of cutaneous advanced glycation end‐products. (27th August 2021) - Bellinato, F.; Maurelli, M.; Gisondi, P.; Girolomoni, G.
Summary: Background: Acquired perforating dermatoses (APDs) are characterized by transepidermal elimination of skin materials. Altered glycation of dermal components may be involved in pathogenesis. Aim: To assess whether patients affected by APDs have increased levels of cutaneous advanced glycation end‐products (AGEs). Methods: A cross‐sectional controlled study involving a total of 109 patients was conducted, enrolling 29 patients consecutively diagnosed with primary APDs [reactive perforating collagenosis (RPC), elastosis perforans serpiginosa (EPS), perforating folliculitis (PF) and Kyrle disease (KD)], 40 age‐ and sex‐matched healthy controls (HCs) and 40 patients with mild atopic dermatitis (AD). The levels of cutaneous AGEs were measured using a validated fluorescence technique. Results: The median skin autofluorescence value in patients with APDs was significantly higher [2.7 arbitrary units (AU), interquartile range (IQR) 1.9–3.9 AU] compared with HCs (1.8 AU, IQR 1.6–2.3 AU; P < 0.001) and patients with AD (2.1 AU, IQR 1.9–2.3 AU; P = 0.01). Median values were 3.5 AU (IQR 2.7–4.6 AU) for RPC, 1.83.5 AU (1.4–2.4 AU) for EPS, 3.1 AU (2.4–4.4 AU) for PF and 2.6 AU (2.3–3.1 AU) for KD. Conclusions: Our results may suggest a possible physiopathological role of AGEs in the transepidermal elimination mechanisms involved in certain APDs. Abstract : Acquired perforating dermatoses (APDs) are characterized by transepidermal elimination of skin materials. Patients with APDs show higher cutaneous advanced glycation end‐products levels compared to the expected value for healthy patients and to patients with mild atopic eczema. Altered glycation of skin materials may be involved in the pathogenesis of certain APDs.